Identification of retinal ganglion cell types and brain nuclei expressing the transcription factor Brn3c/Pou4f3 using a Cre recombinase knock-in allele - Parmhans, Nadia; Fuller, Anne Drury; Nguyen, Eileen; Chuang, Katherine; Swygart, David; Wienbar, Sophia Rose; Lin, Tyger; Kozmik, Zbynek; Dong, Lijin; Schwartz, Gregory William; Badea, Tudor Constantin (The Journal of comparative neurology, 2021)
Members of the POU4F/Brn3 transcription factor family have an established role in the development of retinal ganglion cell (RGCs) types, the main transducers of visual information from the mammalian eye to the brain. Our previous work using sparse random recombination of a conditional knock-in reporter allele expressing alkaline phosphatase (AP) and intersectional genetics had identified three types of Brn3c positive (Brn3c+ ) RGCs. Here, we describe a novel Brn3cCre mouse allele generated by serial Dre to Cre recombination and use it to explore the expression overlap of Brn3c with Brn3a and Brn3b and the dendritic arbor morphologies and visual stimulus response properties of Brn3c+ RGC types. Furthermore, we explore brain nuclei that express Brn3c or receive input from Brn3c+ neurons. Our analysis reveals a much larger number of Brn3c+ RGCs and more diverse set of RGC types than previously reported. Most RGCs expressing Brn3c during development are still Brn3c positive in the adult, and all express Brn3a while only about half express Brn3b. Genetic Brn3c-Brn3b intersection reveals an area of increased RGC density, extending from dorsotemporal to ventrolateral across the retina and overlapping with the mouse binocular field of view. In addition, we report a Brn3c+ RGC projection to the thalamic reticular nucleus, a visual nucleus that was not previously shown to receive retinal input. Furthermore, Brn3c+ neurons highlight a previously unknown subdivision of the deep mesencephalic nucleus. Thus, our newly generated allele provides novel biological insights into RGC type classification, brain connectivity, and cytoarchitectonic.
Keywords: transkripční faktor Brn-3C; Retinal Ganglion Cells; Transcription Factor Brn-3C; periaqueductal gray; zrakové dráhy; retinal ganglion cells; retinální gangliové buňky; Homeodomain Proteins; Visual Pathways; Cre recombinase; deep mesencephalic nucleus; myši; Pou4f3; Mice; homeodoménové proteiny; Gene Knock-In Techniques; integrasy; zvířata; superior colliculus; thalamic reticular nucleus; Alleles; Animals; genový knockin; mozek; alely; Brain; Integrases; transcription factor; Brn3c